Possible mechanisms underlying the decrease in performance associated with overtraining syndrome - Bishop, D.; Grove, J. R.; Russell, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to examine possible mechanisms underlying the performance limiting effects associated with OTS.